2008
DOI: 10.1017/s1743921309031986
|View full text |Cite
|
Sign up to set email alerts
|

Using magnetic activity and Galactic dynamics to constrain the ages of M dwarfs

Abstract: Abstract. We present a study of the dynamics and magnetic activity of M dwarfs using the largest spectroscopic sample of low-mass stars ever assembled. The age at which strong surface magnetic activity (as traced by Hα) ceases in M dwarfs has been inferred to have a strong dependence on mass (spectral type, surface temperature) and explains previous results showing a large increase in the fraction of active stars at later spectral types. Using spectral observations of more than 40000 M dwarfs from the Sloan Di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Delfosse et al 1998;Mohanty & Basri 2003;Reiners et al 2012;West et al 2015;Newton et al 2017). Furthermore, several studies have extended the idea that magnetic activity decreases with age for late-M dwarfs (Fleming et al 1995;Eggen 1990;West et al 2006West et al , 2008aRiedel et al 2017). This indicates that there is an empirical relation between age, rotation and magnetic activity for M dwarfs that may extend to L dwarfs as well.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Delfosse et al 1998;Mohanty & Basri 2003;Reiners et al 2012;West et al 2015;Newton et al 2017). Furthermore, several studies have extended the idea that magnetic activity decreases with age for late-M dwarfs (Fleming et al 1995;Eggen 1990;West et al 2006West et al , 2008aRiedel et al 2017). This indicates that there is an empirical relation between age, rotation and magnetic activity for M dwarfs that may extend to L dwarfs as well.…”
Section: Introductionmentioning
confidence: 90%
“…This relationship is particularly strong when examining the correlations between Galactic height or vertical velocity and age (e.g. West et al 2006West et al , 2008aNordstrom et al 2004;Aumer et al 2016;Yu & Liu 2018). This statistical method was used by several works to obtain kinematic ages of population of stars (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We discuss active cool dwarfs and flaring giants together. M dwarfs are known to have active chromospheres, although old ones get less active (West et al 2008). In addition, Schiavon et al (2005) observed a probable bright, red giant flaring in their spectra.…”
Section: Emission Fill Inmentioning
confidence: 99%
“…For young M stars with Hα emission lines (so-called active M dwarfs), stellar activity has been shown to be tightly coupled with rotation (e.g., Browning et al 2010;Reiners et al 2012). Furthermore, as these stars age and spin down, their Hα emission and variability decrease significantly, offering a diagnostic for distinguishing stellar populations of different ages (West et al 2008(West et al , 2009López-Santiago et al 2010).…”
Section: Introductionmentioning
confidence: 99%